AN ERROR ANALYSIS OF USING SIMPLE PRESENT TENSE IN WRITING HORTATORY EXPOSITION TEXT OF THIRD GRADE STUDENTS - Silaban, Judika; Tampubolon, Sahlan; Siahaan, Sahat Taruli (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
The use of correct grammar in writing Hortatory Exposition texts is crucial for students to effectively convey their ideas. The purpose of this study is to describe grammatical errors about simple present tense based on the taxonomy of surface strategies that occur in hortatory exposition student writing. The researcher used descriptive qualitative. The subjects of this research are students third grade students of SMK swasta jambi Medan. The instrument used in this research is student writing test. The main key in data analysis is the theory of Dulay, Burt, and Krashen. After analyzing the data, the researcher found that there were four types of errors with the percentage of 14(18.42%) addition errors, 7(9.21%) omission errors, 42(55.26%) writing errors and 13(17.11%) sequencing errors. Based on these findings, it can be concluded that writing errors are the most common errors made by students with a percentage of 42 (55.26%). The suggestion that can be given is that teachers and students should learn more about simple present tense so that errors that occur can be minimized. For further researchers, researchers suggest that this research can be a reference in writing further research.